THE EFFECT OF ONE EGG A DAY PROGRAM ON WEIGHT WITH STUNTING IN JETIS VILLAGE - Utami, Dyah Rahmawatie Ratna Budi; Haryoto; Husain, Fida; Utomo, Chandra Wisnu; Utomo, Maryatun (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Background: The nutritional status of toddlers is an important indicator of public health. Malnutrition during infancy can impact growth, cognitive development, and the risk of chronic disease in the future. Eggs are a source of high-quality animal protein and have the potential to be a simple intervention to improve the nutritional status of toddlers. Objective: To determine the effect of the 1-egg-a-day program for 1 month on the weight of stunted toddlers. Methods: A quasi-experimental study with a pre-test, post-test, and control group design was conducted on 18 toddlers aged 6–59 months in Jetis Village. The intervention group was given 1 boiled egg daily for 30 days, while the control group received no intervention. Weight was measured using a calibrated scale. Data analysis used a paired t-test due to the normally distributed data. Results: The average weight gain of toddlers was 0.3 kg with a p-value of 0.0001. The highest increase was 0.8 kg. Conclusion: The 1-egg-a-day program for 1 month had a significant effect on weight gain of toddlers in Jetis Village.